Effect of p53 activity on the sensitivity of human glioblastoma cells to PARP‐1 inhibitor in combination with topoisomerase i inhibitor or radiation. Issue 11 (2nd September 2014) - Sabbatino, Francesco; Fusciello, Celeste; Somma, Domenico; Pacelli, Roberto; Poudel, Ravin; Pepin, David; Leonardi, Antonio; Carlomagno, Chiara; Della Vittoria Scarpati, Giuseppina; Ferrone, Soldano; Pepe, Stefano
Abstract Poly (ADP‐Ribose) polymerase‐1 (PARP‐1) is involved in the DNA repairing system by sensing and signaling the presence of DNA damage. Inhibition of PARP‐1 is tested in combination with DNA damaging agents such as topoisomerase I inhibitors or ionizing radiations (RT) for the treatment of glioblastoma (GBM). Disruption of p53, widely prevalent in GBMs, plays a major role in DNA repairing system. The current study investigates whether p53 activity has an effect on the sensitivity of human GBM cells to PARP‐1 inhibitors in combination with topoisomerase I inhibitor topotecan (TPT) and/or RT. Human GBM cell lines carrying a different functional status of p53 were treated with PARP‐1 inhibitor NU1025, in combination with TPT and/or RT. Cytotoxic effects were examined by analyzing the antiproliferative activity, the cell cycle perturbations, and the DNA damage induced by combined treatments. PARP inhibition enhanced the antiproliferative activity, the cell cycle perturbations and the DNA damage induced by both TPT or RT in GBM cells. These effects were influenced by the p53 activity: cells carrying an active p53 were more sensitive to the combination of PARP inhibitor and RT, while cells carrying an inactive p53 displayed a higher sensitivity to the combination of PARP inhibitor and TPT. Our study suggests that p53 activity influences the differential sensitivity of GBM cells to combined treatments of TPT, RT, and PARP inhibitors. © 2014 International Society for Advancement of Cytometry